TAFSIR NUSANTARA Q.S AR-RUM AYAT 41: MENYIKAPI ISU SAMPAH DI BANJARMASIN - Ahmad Ridhoni; Ahmad Ridhoni, Mahathir Bin Udar, Muhd. Firdaus Bin Roziman, Ahmad Mujahid (CV. Adiba Aisha Amira, 2025)
The environmental crisis caused by poor waste management has become a major issue in Banjarmasin City, South Kalimantan, particularly following the closure of the Basirih Final Waste Processing Site (TPAS). This study aims to examine the meaning of Surah Ar-Rum verse 41 and contextualize it with the ecological damage resulting from waste issues in Banjarmasin. The research uses a qualitative-descriptive approach based on library research, with the verse analyzed through three Nusantara (Indonesian) interpretations: Tafsir al-Mishbah, Tafsir al-Azhar, and the interpretation by the Indonesian Ministry of Religious Affairs. The findings reveal that the term fasād in the verse reflects various forms of damage like physical, moral, and spiritual caused by human actions. The local context of Banjarmasin shows the real impact of the waste crisis, both on land and in rivers, aligning with the verse’s meaning. The analysis is carried out through three perspectives: ecological, sociological, and theological. Ecologically, Islam calls for responsibility in preserving the environment. Sociologically, the low level of public awareness is the main cause of the problem. Theologically, this destruction serves as a divine warning for humans to return to the right path. This study asserts that waste management in Islam is not merely a technical issue but a form of spiritual responsibility as stewards (khalifah) on Earth. Solutions to the waste crisis must involve collaboration between the government, religious leaders, and the community, based on faith awareness and Qur’anic values